Distribuição genômica e antigênica do BHV5 em encéfalos bovinos com meningoencefalite não supurativa: casos clínicos - Giroto, Tássia de Paula [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Meningoencephalitis caused by bovine Herpesvirus 5 (BHV5) has been described worldwide. The disease occurred as outbreaks of isolates clinical cases. In Brazil, encephalitis caused by BHV5 has been confirmed by the increase of positive animals, being the second major cause of bovine viral encephalitis. Likewise, the aim of this study was to characterize brain regions from central nervous system (CNS) presenting high frequency of BHV5 antigen and genome, phenotype lymphocytes subpopulations among perivascular cuffs and compare these results with cytokines transcription. The samples (n=8) were submitted to histopathological analysis, immunohistochemistry and molecular evaluation. The main histopathological lesions were characterized as perivascular cuffs, classified as severe, and sometimes moderate. All cases, perivascular infiltrates were severe in olfactory bulb, and frontal, temporal and parietal lobes. The cytokines expression was considered up regulated in olfactory bulb and piriform lobe. This study addressed the BHV5 distribution mainly observed in frontal regions from CNS, what confirmed the respiratory route as important for virus infection.

A meningoencefalite por herpesvírus bovino 5 (BHV5) foi descrita em várias regiões do mundo. A doença ocorre na forma de surtos ou de casos isolados. No Brasil, encefalites causadas pelo BHV5 têm sido confirmadas de forma crescente nos rebanhos, sendo considerada a segunda maior causa de encefalite com etiologia determinada em bovinos. Nesse sentido, o presente estudo objetivou caracterizar as regiões do sistema nervoso central (SNC) com maior freqüência do BHV5, o envolvimento de diferentes populações de lincócitos e a expressão de citocinas relacionadas ao processo inflamatório. As amostras (n=8) foram submetidas às análises histopatológica, imuno-histoquímica e molecular. A principal lesão observada foi caracterizada como infiltrado perivascular, classificado em leve, moderado e severo. Em todos os casos o infiltrado perivascular foi notado de forma severa no bulbo olfatório, lobos frontal, temporal e parietal. A expressão de citocinas foi principalmente detectada nas regiões do bulbo olfatório e lobo piriforme. Este estudo abordou que a incidência do BHV5 ocorreu principalmente na região frontal, visto que a contaminação pelo vírus ocorre de forma nasal, tendo como primeiro contato a região frontal do cérebro com o BHV5.
Genomic and antigenic distribution of BHV5 among bovine brains with non-suppurative meningoencephalitis: clinical cases
Keywords: Bovine herpesvirus 5; Brain; Cytokines; Herpesvírus bovino 5; Encéfalo; Citocinas